Some Problems of Assessment of The Efficiency of Using Electronic Educational Resources - Nurova Muxabbat Mardiyevna (Genius Publishing Group, 2022)
Electronic educational resources (EER) reduce the time for mastering educational material, their advantages and disadvantages, as well as systems of synchronous electronic interaction. The complex use of traditional and electronic learning tools will help to form a holistic educational trajectory .Issues of assessing the effectiveness of the use of electronic educational resources, aspects of their application, a determination of their compliance with managerial, organizational,methodological, technological requirements are discussed in the given article.
Keywords: electronic educational resources; self-realization; pedagogical efficiency; training